A Brief Scale to Measure Problematic Sexually Explicit Media Consumption: Psychometric Properties of the Compulsive Pornography Consumption (CPC) Scale among Men who have Sex with Men - Noor, Syed WB (Sex Addict Compulsivity, 2014)
Although the phenomenon of hypersexuality has been described in the literature, and scales of compulsive sexual behavior have been published, the existing measures do not assess compulsive sexually explicit media (SEM) consumption. This study tested the psychometric properties of a new scale, the Compulsive Pornography Consumption (CPC). Exploratory and confirmatory factor analyses results showed good psychometric performance of a five item two factor preoccupation-compulsivity solution. As hypothesized, the scale correlates positively with compulsive sexual behavior, internalized homonegativity, and negatively with sexual self-esteem. The scale will enable researchers to investigate the etiologic factors of compulsive SEM use, and enable clinicians to assess problematic consumption.